“Et vedoando sia donna et madonna”: Guardianship and Remarriage in Sixteenth-Century Venice - Bellavitis, Anna (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
Widowhood and Guardianship The Roman law was very clear: widows couldn’t have guardianship of their minor children, because, according to Yan Thomas’ interpretation, the juridical capacity of women was limited to their own person. In fact, in most cases, Roman widows or divorced women kept their children with them, to bring them up and to educate them, but there was always a male guardian, to whom accounts could be asked.